2020
DOI: 10.1590/0034-761220180157x
|View full text |Cite
|
Sign up to set email alerts
|

Public sector accounting reform in Latin America and Epistemic Communities: an institutional approach

Abstract: Latin American countries have undergone a growing interest in international accounting standards. Several countries are making progress in the adoption of international standards driven by different internal factors as well as external dynamics. The role of experts in the design of public policies associated with international standards has been studied by the epistemic community theory, which is the theoretical framework used in this study to address the influence of different international organizations on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Previous studies demonstrated that neither workers nor management have adequate financial and human resources for the implementation of the accrual-based IPSAS, which leads to the top management withholding commitment to the implementation of the accrual-based IPSAS (Ahmad and Nasseredine, 2019; Azevedo et al , 2020a, 2020b; Harun, 2007; Ismaili and Ismajli, 2020; Tetteh et al , 2021; Thanh et al , 2020; Yuliati et al , 2019). The resistance to change is one of the barriers (Al-otoom and Alrabba, 2022; Brito and Jorge, 2021; Tetteh et al , 2021) because the age of senior managers has a negative impact on accounting implementation (Neves and Gómez-Villegas, 2020) for fear of losing control over the budget authority (Adhikari et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that neither workers nor management have adequate financial and human resources for the implementation of the accrual-based IPSAS, which leads to the top management withholding commitment to the implementation of the accrual-based IPSAS (Ahmad and Nasseredine, 2019; Azevedo et al , 2020a, 2020b; Harun, 2007; Ismaili and Ismajli, 2020; Tetteh et al , 2021; Thanh et al , 2020; Yuliati et al , 2019). The resistance to change is one of the barriers (Al-otoom and Alrabba, 2022; Brito and Jorge, 2021; Tetteh et al , 2021) because the age of senior managers has a negative impact on accounting implementation (Neves and Gómez-Villegas, 2020) for fear of losing control over the budget authority (Adhikari et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Asimismo, More & Morey (2021) infiere que suele ser entendida como la capacidad de articular todos los elementos institucionales con la finalidad de optimizar y llevar a cabo las habilidades de tal manera que se puedan cumplir las metas propuestas. En cambio, Neves & Gómez (2020) precisa que está referida a la facilidad con la que los colaboradores de una organización diseñan e implementan una propuesta estratégica mediante el Presupuesto Institucional. Por su parte, Cubero & Valdez (2022) aluden que es una serie de acciones mediante el cual una entidad direcciona de manera fehaciente y objetiva sus actividades hacia el alcance de sus propósitos.…”
Section: Bases Teóricas De La Investigaciónunclassified
“…A vast number of organizations adopt systems or processes to resemble leading entities, due to environmental pressure or as the result of expert action, all of which are known as institutional isomorphism (DiMaggio and Powell, 1983). Some research has accounted for the causes and results of adopting and implementing IPSAS, showing divers results (Baskerville and Grossi, 2019;Neves and Gómez-Villegas, 2020). Such a context makes it essential to identify and systematize the literature addressing IPSAS adoption processes from an institutional perspective to identify and compare factors and conditions in common that help explain and understand the choice of the accounting model for the public sector.…”
Section: Sociologicalmentioning
confidence: 99%
“…IPSAS appear as a technical innovation because they incorporate the accrual accounting criterion into public information systems, which traditionally observed the cash criterion. Nevertheless, from the perspective of institutional theory, the IPSAS adoption program is seen as a legitimization process rather than a technical rationalization process (Neves and Gómez-Villegas, 2020).…”
Section: Introductionmentioning
confidence: 99%